Implementasi Digital Marketing pada UMKM “Otak Otak Singapur” di Bengkalis - Jhonatan Jhonatan; Erma Domos (Politeknik Kampar, 2025)
This Community Service activity aims to implement a digital marketing strategy for the Otak Otak Singapur SME in Bengkalis to expand market reach and increase product sales. The methods used include SWOT and STP analysis to assess the internal and external conditions of the business, as well as the implementation of digital marketing strategies through various platforms such as Instagram, Facebook, Google My Business, and the Maxim marketplace. Based on insight data analysis, the Instagram account reached 846 accounts with 81.8% new users, Facebook gained 546 active followers, Google My Business recorded 174 interactions, and Maxim played a key role in simplifying the ordering and product delivery process to consumers. The STP strategy focuses on targeting the youth segment and food enthusiasts, positioning the product as a unique and authentic grilled snack. The results of the activity show a significant increase in business visibility, customer interaction, and purchase interest. The contribution of this activity is the implementation of a data-driven digital marketing strategy that is effective, applicable, and sustainable, which can serve as a model for other SMEs facing business competition challenges in the digital era.